Expression of a nonagglutinating fimbria by Proteus mirabilis. - Tolson, D L (1995)
We have clarified growth conditions and isolation strategies for the nonagglutinating fimbriae from Proteus mirabilis. Nonagglutinating fimbriae were expressed by all P. mirabilis strains we examined, and the major subunit proteins, which ranged from 23 to 29 kDa as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, had highly conserved N-terminal sequences.